DETERMINAN HARGA EMAS - Sunaryo, Sunaryo (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2022)
The purpose of this research was to determine the effect of Gold Demand, Exchange Rates, Interest Rates and Inflation on Gold Prices. The sample is based on quarterly time series data from the first quarter of 2010 to the fourth quarter of 2019, with documentation data collection technique from PT Aneka Tambang, Tbk and Bank Indonesia. Analytical techniques used were multiple regression. The result of t-test shows that the Gold Demand and Interest Rate have positive significant effect on Gold Price. Interest Rate have negative significant effect on Gold Price. Inflation have no significant effect on Gold Prices.